Carbon-carbon bond activation at chromium(I): an 11-electron complex cleaving dialkynes - Braun, Felix; Bruckhoff, Tim; Ott, Jonas C.; Ballmann, Joachim; Gade, Lutz H. (Angewandte Chemie. International edition, 2024)
An 11-electron T-shaped chromium(I) complex was obtained by reduction of a PNP-supported chromium(II) iodide complex. Its d5 high-spin electronic structure was characterized employing paramagnetic NMR, EPR, UV/Vis and magnetic measurements (SQUID). The complex readily reacts with conjugated dialkynes to cleave the internal C−C bond, forming the respective acetylide complexes. Varying the alkyne substituents enabled the isolation and characterization of dinuclear dialkynedichromium intermediates which thermally convert to the products.
Online verfügbar: 28. Oktober 2024
Gesehen am 13.05.2025